DANCE: AN ART AND A WAY OF CARING THE BODY (Fiep Bulletin - online, 2013)
One of the hallmarks of the contemporary man is continually seeking ways to take care of the body. People want a well-shaped body, a healthy body, a body socially presentable. The demand for gyms, exercises accompanied by professionals or not, a more appropriate feeding are major ongoing challenges to reach such goals. This article presents the dance, an art as old and modern, as a way of taking care of the body. Among many possibilities to present dances in Brazilian culture, due to its cultural diversity, we discuss here samba and jongo as two expressions linked to African roots, highlighting their particular contributions to the development of caring for the body. The research is a literature review combined with everyday experiences, and the results show that samba and jongo, as ways of caring for the body, are still little used in the educational process in Brazilian schools, especially in physical education.
Keywords: dance; body; care